Genese, Verlauf und Symptome der Alkoholkrankheit am Beispiel des Romans "Der Trinker" von Hans Fallada - Łyjak, Konrad (Acta Neophilologica, 2021)
The aim of this article is to analyze the alcohol addiction of Erwin Sommer, the main character in the novel The Drinker by Hans Fallada. This article focuses solely on his alcohol-related problems, and not on that of his temporary stay in prison or in sanatorium. The analysis of Sommer’s alcohol addiction is based not only on literary studies and the biography of the writer but most of all on current medical studies concerning alcoholism. I also compare Erwin Sommer with another classic figure with respect to literature about alcoholism – Jack London and his famous autobiographical novel John Barleycorn. Although the symptoms of alcoholism by Erwin Sommer are actually typical, the aetiology of his alcohol addiction is not so obvious. For this reason, I attempt to discover the real genesis of his disease. The basis of my considerations are, among others, the classification of alcohol disease stages, developed by E. M. Jellinek, the precursor of alcoholism studies, the International Statistical Classification of Diseases and Related Health Problems ICD-10 created by the World Health Organisation (WHO) and the S3-Guideline, published by the Association of the Scientific Medical Societies, German Society of Psychiatry, Psychotherapy, Psychosomatics and Neurology, and German Society of Addiction Studies and Addiction Therapy. In current scientific articles and studies about alcohol-related problems, one can find plenty of details which are very helpful to fully understand Hans Fallada’s life and his fascinating and frightening report about the social, financial and personal fall of a human being.